A Comparative Effect of Child-to-Child and Health Educator to-Child Teaching Approaches on Nutritional Status in Elementary School Students - Mandana Farrokhmanesh; Nasrin Mokhtari Lakeh; Shahla Asiri; Ehsan Kazem Nezhad Leyli; Alireza Ghaemi; Siamak Afzali (Guilan University of Medical Sciences, 2018)
Introduction: Nutritional problems are one of the most important health issues among school-aged children, and modification of the nutritional status in children is as well important. Objective: Present study aims to determine the effectiveness of child to child teaching approach as compared to educator to child teaching approach on promotion of nutritional status of elementary school students in Rasht city in 2014-15. Materials and Methods: This is an educational trial study. Samples were chosen by random-cluster sampling model through which 452 students aging 9-11 years were selected from third, fourth and fifth grades from elementary schools of different districts of Rasht. Tools consisted of demographic questionnaire and food frequency questionnaire (checklist) with 54 items on snacks. From 452 students, 188 students with unfavorable frequency were divided into three groups; 62 students in child-to-child group, 68 students in health educator-to-child group and 58 students in control group. An educational package (including pamphlets, booklets and posters) was taught by researcher on food pyramid, healthy and unhealthy snacks using role play and fruit festival conducted in three sessions each lasting 30 minutes for three level elementary students and health educators. Of course the control group received no intervention. Data was analyzed by descriptive and inferential statistics such as Chi Square, Mann Whiteny ans Kruskal Wallis tests. Results: The differences of mean in score changes before and after education in child to child group was more effective than educator to child teaching group (P=0.001). Based on food frequency score obtained on nutritional status after teaching, the health educator to child group performed better than other groups (P=0.014). Conclusion: Study findings indicated that child to child teaching was close to the performance of health educators in relation to promotion of nutritional status and favorable food frequency. Therefore in attention to potential ability of children in teaching, they can improve school health programs along with educator to child teaching approach.